Towards knowledge management implementation at UPP-ICT : Building a visual computer hardware specification system / Haliza Binti A Hamid - Haliza, A Hamid (2004)
This project is building a visual computer hardware specification system. This system was developed due to the problems that arise using the manual process, user hard to find the information up-to-date and difficult to get timely information of computer hardware specifications. It done manually using hardcopies on paper with not has the complete information about the specification and no pictures of the hardware. The user and administrator is the actor of this system. The objectives of this project are to identify knowledge sources within computer hardware domain. To perform add, modify and delete operator on data in the information repository so as to keep it up to date. Next, to provide information for preparation of computer hardware specification and user guide for user in imderstanding computer hardware specification. It also provides a search and retrieve mechanism relevant information regarding computer hardware specification. The methodology that used to develop this project is data collection, specification building, design, build coding and testing. By implementing this project, user can get more knowledge about the computer hardware specification. This system also gives convenience for users in seeing and knowing how the real the computer hardware is.